Wykorzystanie łańcuchów Markowa do oceny ryzyka kredytowego - Wójciak, Mirosław (Use of Markov chains to estimate credit risk level, 2007)
Credit migration or transition matrices, which characterise past changes in credit quality of firms, are cardinal inputs to many risk management applications. It means that the main stress is to choose the right estimation method. The paper presents a few methods of transition matrices estimation due to appropriate method choice. Multi-binding Markov chains are described together with non-homogeneous Markov chains. The article presents also a continuous-time credit migration estimation method which enables to use Markov chains in case of less numerous data bases.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 134-146